Predictors of intention to stay among executives in Malaysian manufacturing organizations and moderating effect of intergenerational workforce - Yong, See Chen (2017)
The high average yearly turnover rate of executive employees in the Malaysian manufacturing organizations can destroy their competitiveness in the marketplace. Issues related on the efforts in increasing employees’ intention to stay have become more critical when younger generations such as Generation Xers and Generation Yers employees are likely to quit their jobs more frequently compared to Baby Boomers. Previous study found that Malaysian employees are willing to remain in their current organizations only for less than three years. The objective of this study is to investigate the predictors of intention to stay and the moderating roles of a multi-generational workforce among executive employees in the Malaysian manufacturing organizations. Hence, this study examined how human resource practices and job-related factors influence an individual’s intention to stay, and the moderating roles of a multi-generational workforce on the relationship between the selected independent variables and intention to stay. Investigation from this study generated both theoretical and practical significance which improved insights on intention to stay. This study applied Herzberg’s Two-Factor theory, Robert Agnew’s General Strain theory, and Generational Cohort theory in order to provide an integrative theoretical framework in explaining executive employees’ intention to stay in the Malaysian manufacturing organizations. The present study adopted a quantitative approach with descriptive correlational research design. In addition, it employed a cross-sectional survey using self-administered questionnaire in data collection. A number of 456 executive employees from manufacturing organizations in the three sub-sectors which include palm oil, electrical and electronics, and refined petroleum products participated in this study. The results of their responses were analyzed using descriptive and AMOS-SEM analysis. The findings indicated the level of intention to stay was reasonably high among the respondents. The results in the AMOS-SEM structural model path revealed that pay and compensation, and career advancement (human resource practices), and role conflict and role ambiguity (job-related factors) significantly influenced executive employees’ intention to stay. However, performance appraisal (human resource practice) did not contribute significantly towards executive employees’ intention to stay. Moreover, the findings also indicated that pay and compensation (human resource practice) and role conflict and role ambiguity (job-related factors) were moderated by the multi-generational workforce. Employers need to be aware that Generation Xers are highly affected by pay and compensation and role ambiguity, while Generation Yers are strongly affected by role conflict. The findings of this study have highlighted the pay and compensation, career advancement, role conflict, and role ambiguity are among the key factors that need to be prioritized in the retention practices by HRD practitioners to focus on to increase intention to stay among their internal labor pool. Improving the employees’ retention strategies and increasing intention to stay among the employees would provide an added value on HRD practices in Malaysia, specifically, those in the manufacturing organizations.